The Effect Of Service Quality And Customer Experience On Pdam Customer Satisfaction In Patas I Village, Gunung Bintang Awai District, Central Kalimantan Province - Norlina; Wafa, Faqih El; Muhammad Rizali; Radiansyah (CV. SINAR HOWUHOWU, 2025)
Customer satisfaction is very important for business development. Customer experience refers to the overall customer experience, while service quality is an important factor and the main cause of customer satisfaction. However, there are several problems at the PDAM in Patas 1 Village, namely when customers report damage and request repairs, the response is very slow and may not be responded to at all. When damage or repairs are needed at PDAM, no notification is given, which can take up to 2-3 days to resolve. As a result, the water may have a strong lime/chlorine odor, which could potentially affect customer satisfaction. This study aims to determine whether service quality and customer experience simultaneously and partially affect customer satisfaction. The type of research used is field research with a quantitative approach, using a questionnaire technique for data collection. The population in this study is PDAM customers, with a sample size of 86 respondents. The results of this study indicate that the service quality variable does not have a significant effect on customer satisfaction, in the sense that the better the service quality provided by PDAM Desa Patas 1, the less it affects the satisfaction obtained. Then, the customer experience variable has a positive and significant effect on customer satisfaction, indicating that the more positive the customer experience, the higher their level of satisfaction tends to be. Simultaneously, service quality and customer experience affect customer satisfaction